Prescription Analysis in Diabetes Mellitus - SAHOAHOO SUBHASISH,; DASH KIRAN KAUSHIK,; SAHOO SABITA,; SAHU DEBASISH, (International Journal of Pharma and Bio Sciences, 2010)
A study was carried out in medicine ward (in patient) of a Government Hospital, Orissa. A total of 60 patients were enrolled in the study. Of them 42 were male & 18 were female patients. The male patient were greater in number than female. According to the age distribution of patients the study was carried out in the range of 10-80 years. More numbers of patients were seen in range of 51-60years.The most common occurrence of diseases found in the medicine ward type-2 Diabetes mellitus with Coronary artery disease, hepatomegaly and others. The drug interaction and some adverse drug reactions were reported. Cost of the therapy per day also included in this study.